The first day of eternity [large type] - West, Charles (West, Charles. Hunters series, 2024)
"His Crow name was Crazy Wolf. Orphaned after losing his family in an Indian attack, young Cody Hunter found a loving home among the Crow people -- and learned the ancient ways of the Crow trackers. His well-honed skills earned him a place in the U.S. Army as a valued scout. But now, after fifteen years of living his life as Crazy Wolf, Cody is ready to face his painful past. He will return to the place that still gives him nightmares -- and where the dreams of his father ended in bloodshed . . . High in the mountains of Montana, Cody finds a stone memorial erected by the survivors of the families slaughtered there. The site of the attack triggers Cody's darkest memories -- and leads him to a stunning realization: his father and two brothers did not die on that day. They may still be alive. And he will stop at nothing to find them again. To follow in their footsteps. To track them down on the treacherous journey west. A search this deadly may be the craziest thing Crazy Wolf has ever done. But he is a born Hunter -- and he's willing to die that way. . . ."--